Well-Being of Academic Staff in Teaching and Research Roles: A PERMA Model Analysis in Higher Education - Zeid, Adam (Dobrostan pracowników akademickich w rolach dydaktycznych i badawczych: analiza przy użyciu modelu PERMA w szkolnictwie wyższym, 2025)
Aim: This study aimed to identify how the dual professional roles of academic staff, as educators and researchers, are associated with their well-being within higher education institutions. Methodology: A quantitative approach was used based on the adapted PERMA Profiler questionnaire, distributed among 140 academic employees at a single Polish university. The responses were analysed using descriptive statistics, paired t-tests, effect size measurements, and correlation analyses to compare well-being between teaching and research roles. Results: The findings indicated that academics experience higher levels of Positive Emotions, Meaning, and Accomplishment in teaching than in research. No significant differences were found in Engagement and Relationships between the roles. Correlations ranged from low-to-moderate (Positive Emotions) to strong (Relationships), indicating partial but uneven consistency of well-being across roles. Implications and recommendations: The study highlights the need for institutional strategies that recognise and support the well-being of academic staff in both teaching and research contexts. Since teaching and research involve different requirements, separate assessment of these aspects allows institutions to balance these roles more effectively, tailor support and avoid applying one-size-fits-all solutions. Future research should include comparative and longitudinal studies across institutions, as well as qualitative exploration of coping mechanisms used by the faculty. Originality/value: This study provides role-specific insights into academics’ well-being through an intra-individual comparison of their teaching and research roles. The use of adapted PERMA framework allowed for the identification of well-being patterns across the dual roles, which may be otherwise masked, especially if aggregated approach to measuring well-being is used.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 4, s. 151-165
Keywords: well-being; PERMA; higher education institutions; academic staff; teaching and research; dobrostan; szkolnictwo wyższe; kadra akademicka; dydaktyka i badania naukowe